Quality characteristics of alpaca (Vicugna pacos) fibre. As an indicator of its marketability - Luis Alonso Chicaiza Sánchez; Patricia Marcela Andrade Aulestia; Rafael Alfonso Garzón Jarrin (Journal of the Selva Andina Animal Science)
To evaluate the main characteristics of alpaca (Vicugna pacos) fibre quality as an indicator of its marketability, this research was carried out between June and July 2022, in the province of Cotopaxi, Ecuador. Sixty alpacas were selected from 12 communities. The diameter, length, fibre categorization and fleece weight were taken from existing records; except in Salache, where 10 ± 0.1 g of fibre was collected from the animals' left midribs. The fibre was classified and its marketing category was determined, according to the marketing company. Descriptive statistics were obtained for each variable. The lowest diameter values corresponded to Apahua (16.06 ±1.30 µm) and the highest to Salache (32.00 ±3.26 µm). The longest fibre length was found in the alpacas of Salache (15.56 ±1.10 cm) and in the rest of the communities it ranged from 9.16 to 13.16 cm. The highest average fleece weight was obtained in Salache (4.25 ± 0.45 kg) and the lowest in Maca Chico (1.89 ± 0.18 kg). In the Kum company, the Sacha community contributes 48.87 % of the extra fine fibre, and 44.14 % of the total. In the Pacocha company, the Apahua community contributed 43.37 % of the total fibre and 26.15 % of the superior quality fibre. It can be concluded that the fibre from the alpacas of Apahua has the smallest diameter, length and fleece weight. This community sold the highest quality fibre.